The effectiveness of front fork systems at damping accelerations during isolated aspects specific to cross-country mountain biking - Macdermid, P. W.; Miller, M. C.; Fink, P. W.; Stannard, S. R. (Sports Biomechanics, 2017)
Cross-country mountain bike suspension reportedly enhances comfort and performance through reduced vibration and impact exposure. This study analysed the effectiveness of three different front fork systems at damping accelerations during the crossing of three isolated obstacles (stairs, drop, and root). One participant completed three trials on six separate occasions in a randomised order using rigid, air-sprung, and carbon leaf-sprung forks. Performance was determined by time to cross obstacles, while triaxial accelerometers quantified impact exposure and damping response. Results identified significant main effect of fork type for performance time (p<0.05). The air-sprung and leaf-sprung forks were significantly slower than the rigid forks for the stairs (p<0.05), while air-sprung suspension was slower than the rigid for the root protocol (p<0.05). There were no differences for the drop protocol (p<0.05). Rigid forks reduced overall exposure (p<0.05), specifically at the handlebars for the stairs and drop trials. More detailed analysis presented smaller vertical accelerations at the handlebar for air-sprung and leaf-sprung forks on the stairs (p<0.05), and drop (p<0.05) but not the root. As such, it appears that the suspension systems tested were ineffective at reducing overall impact exposure at the handlebar during isolated aspects of cross-country terrain features which may be influenced to a larger extent by rider technique. ABSTRACT FROM AUTHOR